Numerical considerations on the modeling of source and boundary conditions for the frequency domain visco-acoustic wave equation solution (2018)
ABSTRACT: Seismic modeling is an important step in the process used for imaging Earth subsurface. Current applications require accurate models associated with solutions of the wave propagation equation in real media. Unfortunately, it is common not to find in the technical literature deep discussions on the impact of specific details associated with the physical modeling of some crucial ingredients of the process, such as seismic source term and boundary conditions. In this paper, we discuss some issues related to the modeling of wave propagation in visco-acoustic media using finite differences. We focus our attention on two major elements of the modeling problem that are associated to the source term and the boundary conditions. We show that the source term can be modeled using a scale parameter that controls the spread of energy and shows that this parameter is a function of frequency and position of the source. As to boundary conditions, we show that Perfectly Matched Layer (PML) parameters are also frequency dependent. For both cases, seismic source scale parameter and PML model parameters we provide values and functions that optimize the performance of the approach for problems where visco-acoustic wave propagation is required. Frequency domain Full Waveform Inversion (FWI), or Reverse Time Migration (RTM) processes that depend fundamentally on the appropriate modeling of the wave-field are potential fields of application of these results.